Preventive effects of Allium hirtifolium Boiss methanolic and aqueous extracts on renal injury induced by lead in rats - Nafise Hajian; Zahra Rezayatmand; Kahin Shahanipur (Shahrekord University of Medical Sciences, 2018)
Introduction: In this study the kidney protective effects of methanolic and aqueous extracts of Allium hirtifolium Boiss (shallot) were evaluated on kidney toxicity induced by lead (Pb) in Wistar rats. Methods: Eighty adult female Wistar rats of 3-5 months of age and weighing 200-250 g were allocated randomly into 10 groups and treated for 15 and 30 days as follows: control group, Pb (10 mg/L), methanolic extract of shallot (12.5 mg/kg and 25 mg/kg), Pb plus methanolic extract of shallot (12.5 mg/kg and 25 mg/kg), aqueous extract of shallot (12.5 mg/kg and 25 mg/kg), Pb plus aqueous extract of shallot (12.5 mg/kg and 25 mg/kg). Serum concentrations of glucose as well as renal parameters were measured at 15 days and 30 days in the studied groups. Results: Analysis showed a significant reduction in the mean of urea in the methanolic extract group with a concentration of 12.5 mg/kg, compared to the lead group. Consumption of 25 mg/kg methanolic extract of shallot showed a significantly reduction of uric acid, creatinine and total protein in comparison with control group and lead group. Consumption of 25 mg/kg methanolic extract of shallot+lead was able to reduce the mean of urea uric acid, creatinine and total protein in comparison with lead group. Also, the results showed that methanolic extract of shallot+lead at a dose of 12.5 mg/kg could reduce the mean of urea uric acid, creatinine and total protein in comparison with lead group. There was no significant difference in the rest groups. Conclusion: The results of the study showed that shallot extract can dose dependently reduce the factors related to lead induced renal damages.